PROTOTYPE ALAT PENYORTIR BIBIT IKAN LELE BERBASIS ARDUINO UNO - Ahmad Zari Ulhisaf; Nurwahid Syam; Adi Candra (Journal System Information And Computer, 2023)
Abstract – This study aims to: (1) design a tool capable of sorting catfish seeds. (2) find out the results of testing the aruino uno catfish seed sorting tool. This study used a prototype research method (prototyping). The stages of making a tool using a prototype are gathering needs, fast design process, building prototypes, evaluating and repairing. This study used data collection techniques, namely observation, interviews, literature study, questionnaires, documentation. The results showed that: (1) the prototype of the catfish seed sorting tool used the LDR sensor, KY-008 sensor and Arduino Uno, namely making a design then assembling tools, doing programming, then testing, then validating or repairing the tool, then testing the tool After that, use the tool. (2) The implementation of the use of the catfish seed sorter uses an LDR sensor, KY-008 sensor, Arduino uno and LCD, to be able to detect and process data and display fish values ​​or work properly.